Evaluasi Capaian Peta Jalan JKN di Provinsi Bengkulu Studi Kasus Sectio Caesarea Tahun 2014 Sampai 2019 - Wulan, Susilo (UI Scholars Hub, 2021)
Bengkulu is one of the provinces in Indonesia where SC rate has increased significantly over the last five years after the implementation of JKN. Previous studies into SC trend in Indonesia indicate that both overutilization and underutilization of SC exist reflected inequality. SC is a public health concern since it absorbs a huge amount of JKN funds and is indicated to contribute to the BPJS deficit. This study evaluates the achievement of the SC case equity target in Bengkulu Province based on the 2014- 2019 JKN roadmap. Combining qualitative and quantitative approaches, analyzing secondary data from the BPJS routine data and government survey (SUSENAS) as well as interview with Local government and BPJS staff. This study found that despite the increase in coverage of JKN memberships, gap exists in the provision of health professionals, doctors and obstetrician distribution likely affected the utilization of SC. Currently, SC is enjoyed mostly by women residing in Bengkulu city and dominated by PPU and PBPU segment, which are 39 and 45% respectively. Improved monitoring and realization of compensation policy to provide equal distribution of doctors and obstetricians either by BPJS or local government.